Influence of the deep cryogenic treatment at the stabilization of martensitic transformation temperatures at the smart material alloy Cu-14Al-4Ni - Nava, Marcelo (2020)
DCT (deep cryogenic treatment) is commonly used in industry to improve the wear resistance characteristics of steels, especially. However, there are just a few researches about the effects on non-ferrous metals. The purpose of this work was to investigate how DCT affects the properties of Cu-14Al-4Ni alloy treated at different soak time and submitted to thermomechanical cycling. A comparative experimental analysis was performed of the thermal properties of alloys obtained on a vacuum furnace, treated by DCT and thermomechanically cyclized. The results indicates that thermomechanical cycling promoted the appearance and growth of the martensitic phase γ'1, less ductile than the martensitic phase β'1, which together with the induced hardening produced an increase in transformation temperatures and microhardness. The higher the number of cycles, the greater these effects. The DCT promoted an increase in the intensity of the diffraction peaks corresponding to the phase β'1 and the maintenance of them during the thermomechanical cycling of the material, which indicates that the DCT stabilizes the martensitic phase β'1 and, consequently, caused a reduction and stabilization of the martensitic transformation temperatures and the microhardness, when compared to the untreated material. The longer the soaking time of DCT, the greater these effects.